Analisis Kepuasan Pengunjung terhadap Produk Crafty Puff pada Kegiatan Bazar Mahasiswa PGSD - Mutiah, Mutiah; Nurfalah, Fadilah; Khairunnisa, Khairunnisa; Intan Safitri, Meiliani; Masti, Indri; Sholihah Rosmana, Primanita (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
This study aims to analyze the level of consumer satisfaction with Crafty Puff products at the Elementary School Teacher Education Program (PGSD) Student Bazaar. This study uses a quantitative descriptive method with data collection techniques in the form of a five-point Likert scale questionnaire given to consumers who purchased the product. There were 23 respondents in this study, selected using accidental sampling techniques. The aspects analyzed include product quality, design, price suitability, purchase satisfaction, repurchase intention, willingness to recommend the product, and service. The data obtained were analyzed using descriptive statistics by calculating the average value for each assessment aspect. The results showed that the level of consumer satisfaction with Crafty Puff products was in the Very Good category with an overall average score of 4.86. The aspects of product neatness and durability, price suitability to quality, and service received the highest scores, while the aspect of using quality materials was in the Fair category. Based on these results, it can be concluded that Crafty Puff products have been able to meet consumer expectations, but efforts to improve material quality are still needed to support competitiveness and future product development.